RELATIONSHIP OF NURSING SERVICES WITH THE LEVEL OF PATIENT SATISFACTION - Dian Wahyuni Desimawati (Sean Institute, 2021)
The purpose of this research was intended to identify the correlation between nursing services and patient satisfaction in Sumbersari Health Center Jember Regency. The sampling technique used purposive sampling and the number of sample were 44 patients in Sumbersari Health Centre. Data analysis technique used chi square test, with significance level of p value = 0.018 (α=0. 05) and OR 10,667. It means that there was a significant correlation between nursing service and patient satisfaction level in Sumbersari Health Center Jember Regency and good nursing service has a chance 10,667 times more in getting higher patient satisfaction.